Pre-Processing Tools and Intelligent Systems Applied to Power Quality Analysis - Fernandes, Ricardo A. S.; Rabêlo, Ricardo A. L.; Barbosa, Daniel; Oleskovicz, Mário; Silva, Ivan Nunes da (IntechOpen, 2011)
None